Pengaruh Pendapatan Asli Daerah (Pad), Dana Alokasi Umum (Dau), Dana Alokasi Khusus (Dak), Dana Bagi Hasil (Dbh), Dan Pertumbuhan Ekonomi Terhadap Pengalokasian Belanja Modal(Studi Empiris pada Provinsi Jawa Tengah Periode 2012-2014) - Dwianto, Agung, Eny Kusumawati,SE,Ak,MM,CA (2017)
The purpose of this study is to provide empirical evidence by using secondary data, regarding the effect of regional income, revenue-sharing, the general allocation fund and special allocation funds to the allocation of capital expenditures. The method used in this research is desriptive analysis method. Data analysis techniques were used to test the hypothesis includes multiple linear regression, F test, R2test and t test. All data collected, processed using the test the classical assumption of normality test, autocorrelation test, multikolinearitas test and heteroskedastisitas test. So that the data did not deviate. Based on the results of statistical test tcalculate probability of PAD as big as 0,564 (p > 0,05), tcalculate probability of DAU as big as 0,000 (p < 0,05), tcalculate probability of DAK as big as 0,016 (p < 0,05), tcalculate probability of DBH as big as 0,022 (p < 0,05) and tcalculate probability of economic growth as big as 0,001 (p < 0,05). This suggests that the DAU, DAK, DBH, and economic growth significant effect on the allocation of capital expenditures. Whereas for the variable PAD no significant effect on the allocation of capital expenditure because it has significant value t > 0,05.